Board Characteristics and Earning Management - Nugroho, Bernardus Y.; P., Umanto Eko (UI Scholars Hub, 2012)
Corporate governance is a concept where management supervision takes place in the decision-making process, both in public and business organizations. This research reviews the effect of board characteristics (measured based on the independent board of directors, dual leadership/CEO duality, board size, managerial ownership, board composition /multiple directorships, board tenure, audit committee, and board interlock) on earning management in companies listed in the Indonesian Stock Exchange during the 2004-2008 period. To identify earning management, the researcher uses the Jones model (1991) as modified by Dechow and Sloan (1996) to separate non-discretionary accrual (NDAC) components from discretionary accrual components (DAC) in the total accrual. The research shows that earning management takes place in companies listed in the Indonesian Stock Exchange during the 2004-2008 period, be they companies in general, manufacturers, non-manufacturers, and companies that use audit committee services. It is discovered that the independent board of directors, board size, managerial ownership, board composition/multiple directorships, board tenure, and audit committee do not affect earning management practices in the above companies; only dual leadership/CEO duality affects the earning management practices.